2015
DOI: 10.1021/acsami.5b01397
|View full text |Cite
|
Sign up to set email alerts
|

Biotin-Triggered Decomposable Immunomagnetic Beads for Capture and Release of Circulating Tumor Cells

Abstract: Isolation of rare, pure, and viable circulating tumor cells (CTCs) provides a significant insight in early cancer diagnosis, and release of captured CTCs without damage for ex vivo culture may offer an opportunity for personalized cancer therapy. In this work, we described a biotin-triggered decomposable immunomagnetic system, in which peptide-tagged antibody designed by chemical conjugation was specifically immobilized on engineered protein-coated magnetic beads. The interaction between peptide and engineered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
62
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(64 citation statements)
references
References 57 publications
(126 reference statements)
1
62
0
1
Order By: Relevance
“…Lu et al developed a biotin-triggered decomposable immunomagnetic system, in which peptide-tagged antibody designed by chemical conjugation was specifically immobilized on engineered protein coated magnetic beads. 19 The interaction between peptide and engineered protein can be reversibly destroyed by biotin treatment, making capture and release of CTCs possible. Quantitative results showed that 70% of captured cells could be released by biotin addition, and 85% of released cells remained viable.…”
Section: Ctc Detection Technologies With Enrichmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Lu et al developed a biotin-triggered decomposable immunomagnetic system, in which peptide-tagged antibody designed by chemical conjugation was specifically immobilized on engineered protein coated magnetic beads. 19 The interaction between peptide and engineered protein can be reversibly destroyed by biotin treatment, making capture and release of CTCs possible. Quantitative results showed that 70% of captured cells could be released by biotin addition, and 85% of released cells remained viable.…”
Section: Ctc Detection Technologies With Enrichmentmentioning
confidence: 99%
“…In addition, the purity of separated SK-BR-3 cells was calculated to be 84 ± 3%. 19 Wen et al fabricated magnetic nanospheres (MNs) by a convenient and highly controllable layer-by-layer assembly method, and successfully captured rare tumor cells in whole blood with an efficiency of more than 94% via only a 5 min incubation (Figure S5). …”
Section: Ctc Detection Technologies With Enrichmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Such approaches share the drawbacks of discounted cell viability and unsatisfied release efficiency. Xie and co‐workers further designed biotin‐triggered decomposable immunomagnetic beads for reversibly capture and release of CTCs . Strep‐Tactin, an engineered streptavidin with biotin‐binding site, could be bound by Strep‐tag II with intrinsic affinity.…”
Section: Ctc Releasementioning
confidence: 99%
“…a) Biotin‐triggered decomposable immunomagnetic beads for reversibly capture and release of CTCs. Reproduced with permission . Copyright 2015, American Chemical Society.…”
Section: Ctc Releasementioning
confidence: 99%